Recycling of steelmaking dusts: The Radust concept - Jalkanen H.; Oghbasilasie H.; Raipala K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Recycling of dusts and other wastes of steelmaking is becoming to a necessity of two reasons: due to high contents of iron oxides dusts are valuable raw material for steelmaking and tightening environmental legislation makes the landfill disposal of wastes more expensive. Fine dust fractions from various stages of steelmaking route contain besides iron and carbon heavy metals especially zinc and lead and heavy hydrocarbons that are acceptable neither for landfill disposal nor for recycling back to processes without any spe4cial treatments. Some theoretical and practical aspects concerning high temperature treatments of steelmaking dusts for removal of hazardous components and production of clean high iron raw material for recycling is discussed in this paper. The Radust technology developed at Koverhar steelwork in Finland for treatment of the most problematic fine fractions of blast furnace and oxygen converter dusts is shortly presented and discussed.